2022
DOI: 10.3390/agronomy12020316
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Compost Amendment Changes Interactions and Specialization in the Soil Bacterial Community, Increasing the Presence of Beneficial N-Cycling Genes in the Soil

Abstract: Significant differences in the microbial community and diversity in soil have been observed due to organic farming, but little research has been performed for exploring microbial functionality and the co-occurrence of patterns among microbial taxa. In this work, we study soil 16S rDNA amplicons from two long-term organic farming systems (Org_C and Org_M) and a conventional system (Conv) to decipher the differences in microbial interaction and network organization and to predict functional genes (principally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…On the other hand, the nitrogen is a key driver of soil microbial community composition ( Fierer et al., 2013 ). The knowledge on microbial N cycling genes in an agroecosystem is crucial to decipher the N cycling in them ( Cuartero et al., 2022 ). In this respect, we found that particular chemical fertilization treatments (IT3 and IT4) significantly increased the abundance of genes contributing to ammonia oxidation ( amoA , amoB , amoC ), that are part of the nitrification process and important for reducing nitrate leaching and emissions of NO and N 2 O ( Liu et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the nitrogen is a key driver of soil microbial community composition ( Fierer et al., 2013 ). The knowledge on microbial N cycling genes in an agroecosystem is crucial to decipher the N cycling in them ( Cuartero et al., 2022 ). In this respect, we found that particular chemical fertilization treatments (IT3 and IT4) significantly increased the abundance of genes contributing to ammonia oxidation ( amoA , amoB , amoC ), that are part of the nitrification process and important for reducing nitrate leaching and emissions of NO and N 2 O ( Liu et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was also a partial negative correlation between fungal species in the OM, which was not found in the CM ( Table 4 ). This negative correlation means that there is competition, exclusion, or adaptation to ecological niches among species (Cuartero et al, 2022 ). However, these negative correlations promote the stability of the microbial network of the soil ecosystem because they compensate for the overexpression of some members.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated microbial alpha-diversity (richness and Shannon index) on rarefied microbial data using the 'trans_alpha' function in microeco. To test the difference between the different locations, we assessed normality and homogeneity of variance using Shapiro-Wilk and Levene's tests using the 'car' package, following the assumptions and using the functions described by Cuartero et al (2022). We performed principal coordinates analysis (PCoA) using the Bray-Curtis distance to visualize the variation in microbial community composition using the 'trans beta' function in 'microeco'.…”
Section: Statistical Analysesmentioning
confidence: 99%